(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the knowledge about the management of health service waste among the professionals of the Basic Health Units of a municipality in the central region of the State of Tocantins, Brazil. It is a descriptive, exploratory study, with a quali-quantitative approach. The interviews were carried out with 89 health workers, being constituted a sample of 26 (29%) nurses, odontologists and doctors, and 63 (71%), professionals with high school education (community health agents, nursing technicians and oral health technicians). Among the workers with higher education 25 (96.1%) interviewed correctly conceptualized the RSS, thus demonstrating knowledge on the subject, however, among the workers with secondary education 48 (76.1%) gave an assertive response, drawing attention in this group the fact that 15 (23.8%) did not answer the question correctly. Waste from health services is still understood as hospital waste by most questionnaires and the perforating ones are the most mentioned.